Aflatoxin Contamination in Animal-Derived Foods and Health Risks - Aydin Rahim (International Journal of Nutrition, 2020)
Aflatoxins (AFs)B1, B2, G1, and G2 are important hepatotoxic mycotoxins produced by Aspergillus flavus, A. parasiticus, and A. nominus. They are converted into metabolites of AFM1, AFM2, B2a, and aflatoxicol by cytochrome P450-related enzymes in the liver after digestion of the feed. These metabolites accumulating in the animal-derived food products such as eggs, milk, cheese, and honey cannot be destroyed by pasteurization or heating process and may influence public health negatively. Therefore, it is very important to prevent or limit the aflatoxin contamination in the animal feeds to decrease the risk of contamination of these metabolites in animal-derived foods.
Keywords: Animal-derived foods